THE CHOICE OF NITRATE THERAPY IN PATIENTS WITH STABLE ANGINA: COMPARATIVE STUDY OF ISOSORBIDE DINITRATE (IN USUAL TABLETS) WITH ISOSORBIDE-5-MONONITRATE (IN VARIOUS PRESENTATIONS) - V. A. Egoro; E. V. Shilova; S. Y. Martsevich (Столичная издательская компания, 2016)
Aim. To study efficacy and tolerability of isosorbide-5-mononitrate (IMN) in various presentations in comparison with isosorbide dinitrate (IDN) in usual tablets in patients with stable angina.Material and Methods. 22 patients (5 women and 17 men) with stable angina of II-III functional class were involved into open randomized comparative crossover study. Patients were split in 3 groups and received each of studied drugs during 4 weeks. IDN (Nitrosorbide, Nizpharm, Russia) in usual tablets 10 mg prescribed for 3 times a day administration; IMN (Monocinque,Berlin-Chemie, German) in tablets 20 mg prescribed for 2 times a day administration. After 1 week therapy the doses of IDN or IMN doubled if it was clinically necessary. Retarded presentation of IMN (Monocinque Retard, Berlin-Chemie, German) in capsules 50 mg prescribed once daily. Drug efficacy was evaluated by changes in clinical symptoms, number of angina attacks, demand in short-acting sublingual nitroglycerin as well as physical activity tolerance.Results. After 4 weeks 18 patients completed study, 2 patients dropped out because of protocol nonobservance and 2 patients dropped out because of side effects (headache). IDN therapy in adjusted dose provided antianginal effect in 15 (83,3%) patients: a number of angina attacks decreased in 39,6%, short-acting nitroglycerin demand reduced in 47,7%. Monocinque in adjusted dose provided antianginal effect in 16 (88,9%) patients: a number of angina attacks decreased in 60%, short-acting nitroglycerin demand reduced in 63%. Monocinque Retard provided good antianginal effect in 18 (100%) patients: a number of angina attacks decreased in 72%, short-acting nitroglycerin demand reduced in 84,8%. There were not significant differences in frequency and severity of headache between studied drugs.Conclusion. IMN therapy with both presentations (administrated 1 or 2 times a day) was more convenient and effective than IDN (administrated 3 times a day).